Effect of different production system on flowering and maturity duration of basmati rice genotypes - Jain, Bharat Taindu; -, Aparajita (ORYZA-An International Journal of Rice, 2019)
The study of G×E Interaction (GEI) is critical for evaluating the mean performance and stability of cultivars across wide range of environmental conditions. An experiment was conducted during kharif 2014-2015 fordiscriminating 22 basmati rice genotypes for days to 50% flowering and days to 75% maturity using AMMI and regression stability models under four different environments viz. direct (DSR-wet) and (DSR-dry) and indirect seeding transplanted rice (TPR) and system of rice intensification (SRI) conditions at CCS HAU farm, Kaul. Estimates of G×E interaction following Eberhart and Russell (1966) and AMMI biplot analysis as per Gauch and Zobel model (1989) were computed. For days to 50% flowering, genotypes like Pusa Basmati 6, Pusa Sugandh 3, Haryana Basmati-1 and Pusa RH 10 were identified under SRI; CSR-30 under DSR (dry) and DSR (wet) and HKR 98-476, Pusa Sugandh 2 and Pusa Sugandh 5 under TPR conditions. However, for days to 75% maturity Pusa Sugandh 3, Pusa Basmati 1121, Pusa Basmati 1 and HKR 06-434 were adapted best to SRI; Traori Basmati, Basmati-370, HKR 98-476 and HKR 06-443 to TPR and DSR (dry) and HKR 06-487 and Pusa RH 10 to DSR (wet).